2019
DOI: 10.1002/chem.201806443
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Separation of Light Lanthanides(III) by Using Bis‐Lactam Phenanthroline Ligands

Abstract: Due to the ever‐increasing demand for high‐purity individual rare‐earth elements, novel and highly selective separation processes are increasingly sought after. Herein, we report a separation protocol that employs shape‐persistent 2,9‐bis‐lactam‐1,10‐phenanthroline (BLPhen) ligands exhibiting unparalleled selectivity for light trivalent lanthanides. The highly preorganised binding pockets of the ligands allowed for the separation of lanthanides with high fidelity, even in the presence of competing transition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…We observed an increased separation factor for the La:Dy mixture solely based on an increased EF solid value, which was EF solid =297±31. This is one of the highest single step enrichment factors known for RE separations . Therefore, this method could potentially be targeted for ultrapure Dy separations/purifications.…”
Section: Resultsmentioning
confidence: 99%
“…We observed an increased separation factor for the La:Dy mixture solely based on an increased EF solid value, which was EF solid =297±31. This is one of the highest single step enrichment factors known for RE separations . Therefore, this method could potentially be targeted for ultrapure Dy separations/purifications.…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the highest single step enrichment factors known for RE separations. [5,18] Therefore, this method could potentially be targeted for ultrapure Dy separations/purifications.M ixtures that contained La:Er-(TriNOx) also gave an extremely large solid enrichment factor of EF La:Er = 202 AE 22 and an overall separation factor of SF La:Er = 471 AE 71. After obtaining separation factors for all of the binary mixtures of La:HRE(TriNOx) complexes,arelationship was observed that generally indicated increasing SF La:HRE performance with the total angular momentum (J) for the free ion of the HRE 3+ cations (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the "inverse sequence" is observed exclusively with structurally rigid materials. For example, Healy et al [20] developed a chelate ligand of the phenanthroline skeleton, wherein the sizecompatibility of ions to the binding space provided by the rigid ligand is more accommodating to the light lanthanide ions as compared to the heavy lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%